Studiu incipient al efectelor fitoterapeutice ale păducelului (Crataegus monogyna) - Corina Marina Kracunovic (Romanian National Association of the Veterinary Products Manufacturers, 2021)
The abundance of scientific evidence has shown that many synthetic drugs can cause serious adverse effects in patients. Lately, the search for natural therapeutic agents with low adverse effects has attracted much attention. Considerable interest has been focused on edible and medicinal plants, which play an important role in human and animal diet and have been used for the treatment of diseases since ancient times. Crataegus monogyna Jacq. (hawthorn) is one of the most important edible plants of the Rosaceae family and is used in traditional medicine. Increasing evidence has shown that this plant has various interesting physiological and pharmacological activities due to the presence of different bioactive natural compounds. Moreover, scientific evidence suggests that hail toxicity is negligible. Therefore, the aim of this paper is to provide a review of the available scientific literature on pharmacological activities, as well as the botanical, phytochemical, and clinical impact of C. monogyna.